Directory of ASTHRDP scholars aquatic (2007-2014), agriculture and natural resources (2013-2014). - Philippines. Department of Science and Technology (DOST). Philippine Council for Agriculture, Aquatic and Natural Resources Research and Development (PCAARRD) (Los Baños, Laguna Philippine Council for Agriculture, Forestry and Natural Resources and Development, Department of Science and Technology, 2015)
This Directory of Scholars, a sequel to the 2013 publication, presents the profile of 166 scholars, both degree and thesis in the aquatic sector from 2007 to 2014; and 18 scholars from the AFNR sector who graduated from 2013 to 2014. It aims to provide access to a pool of experts and more importantly, pave the way for catalyzing cooperative endeavors between and among government and private institutions, R&D centers of excellence; and industry stakeholders.
DOST-SEI Accelerated Science and Technology Human Resource Development Program (ASTHRDP)
Keywords: Research institutes -- Asia -- Directories